2015
DOI: 10.1111/maps.12511
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy, petrology, chronology, and exposure history of the Chelyabinsk meteorite and parent body

Abstract: Three masses of the Chelyabinsk meteorite have been studied with a wide range of analytical techniques to understand the mineralogical variation and thermal history of the Chelyabinsk parent body. The samples exhibit little to no postentry oxidation via Mössbauer and Raman spectroscopy indicating their fresh character, but despite the rapid collection and care of handling some low levels of terrestrial contamination did nonetheless result. Detailed studies show three distinct lithologies, indicative of a genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
74
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 88 publications
(186 reference statements)
10
74
1
2
Order By: Relevance
“…Since no fragments of other petrologic type have been observed so far a classification as a LL6 breccia is appropriate. However, Stubenberg does not belong to the complicated breccias like Almahata Sitta (e.g., Bischoff et al 2010;Horstmann et al 2010;Goodrich et al 2014;Horstmann and Bischoff 2014) or to the complex regolith breccias among the L-and LL-group ordinary chondrites (Bischoff et al 1993(Bischoff et al , 2006(Bischoff et al , 2013aMetzler et al 2010Metzler et al , 2011 and is also different to the LL5-6 breccia Chelyabinsk (Bischoff et al 2013b;Righter et al 2015;Morlok et al 2017). This is consistent with the lack of solar wind implanted noble gases (Fig.…”
Section: Mineralogical Properties and Classification Of Stubenbergmentioning
confidence: 68%
See 2 more Smart Citations
“…Since no fragments of other petrologic type have been observed so far a classification as a LL6 breccia is appropriate. However, Stubenberg does not belong to the complicated breccias like Almahata Sitta (e.g., Bischoff et al 2010;Horstmann et al 2010;Goodrich et al 2014;Horstmann and Bischoff 2014) or to the complex regolith breccias among the L-and LL-group ordinary chondrites (Bischoff et al 1993(Bischoff et al , 2006(Bischoff et al , 2013aMetzler et al 2010Metzler et al , 2011 and is also different to the LL5-6 breccia Chelyabinsk (Bischoff et al 2013b;Righter et al 2015;Morlok et al 2017). This is consistent with the lack of solar wind implanted noble gases (Fig.…”
Section: Mineralogical Properties and Classification Of Stubenbergmentioning
confidence: 68%
“…indicate that the chemical composition of Stubenberg is close to the composition of Chelyabinsk (Righter et al. ) and that the Stubenberg chondrite is not chemically anomalous.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…; Horstmann and Bischoff ; Righter et al. ; Morlok et al. ), where thousands of different pieces reached the Earth's surface, have shown that meteorites can break up in the atmosphere resulting in large meteorite showers.…”
Section: Discussionmentioning
confidence: 99%
“…All three phases have identical composition. The dark lithology was produced by shock-darkening (Kohout et al 2014;Reddy et al 2014;Richter et al 2015). Its reflectance spectrum can mimic carbonaceous material.…”
Section: The Resultsmentioning
confidence: 99%